Śrī Tyāgarājasvāmi kīrtanalu - Tyagaraja, Swami, 1767-1847 (Ummiḍi Śrīranṅgamma : dorakucōṭu, Iṇḍiyan PhainārṭsuSisaiṭi, 1982)
Hymns, with melody (raga) and beat (tala) indications, but without musical notation, to Rama, Hindu deity.